2017
DOI: 10.1002/ange.201705462
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Healable Organogel Nanocomposite with Angle‐Independent Structural Colors

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.Figure 4. Time-lapsed images showing droplet sliding on an inclined blue film of organogel nanocomposite. As liding water droplet was pinned at the damaged area made by blade razor (0-17 s). The droplet continued its journey when the damaged area healed by itself (40-41.5 s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Slippery liquid-infused porous surfaces (SLIPS) show improved damage tolerance (15) with the help of lubricant reconfiguration on the porous substrates; however, these healing mechanisms cannot fully solve the issues of physical damages on solid substrates (16,17). Recently, there are a couple of supramolecular organogels showing persistent self-healing and water-sliding properties under multiple scratches (18,19) because the damaged surface becomes flat after healing, which would facilitate the restoration of surface slipperiness. However, their molecular design does not allow them to repel common hydrocarbon solvents, which will severely affect the lubricating oils that serve as lubricating layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slippery liquid-infused porous surfaces (SLIPS) show improved damage tolerance (15) with the help of lubricant reconfiguration on the porous substrates; however, these healing mechanisms cannot fully solve the issues of physical damages on solid substrates (16,17). Recently, there are a couple of supramolecular organogels showing persistent self-healing and water-sliding properties under multiple scratches (18,19) because the damaged surface becomes flat after healing, which would facilitate the restoration of surface slipperiness. However, their molecular design does not allow them to repel common hydrocarbon solvents, which will severely affect the lubricating oils that serve as lubricating layer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, by taking the advantages of supramolecular chemistry (23,24) in regulating mechanical integrity through reversible cross-linking (25)(26)(27), people have developed silicone-based supramolecular materials with unique features of intrinsic healing, stimuli responsiveness, flexibility, elasticity, and toughness (28). These properties make them promising candidates in the emerging and developed fields, such as artificial skin (29), soft robotics (30), and advanced coating applications (18)(19)(20). However, in accordance with coating applications, current supramolecular silicones lack satisfactory stiffness and mechanical strength, their bonding capacity on various substrates has not been well studied, and the effect of incorporated chemical motifs that provide dynamic bonding on liquid repellency remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure S8, Supporting Information, the reflectance spectra of molten TRPC under different detector angles were measured through the angle changing system of spectrophotometer by fixing the incident angle at 0°. [ 37–39 ] With the increase of detector angle from 10° to 60°, the wavelength changed little and showed the low angle dependence. In our previous study, [ 40 ] the diffuse reflectance spectra of SnO 2 inverse opal showed low angle dependence.…”
Section: Resultsmentioning
confidence: 99%
“…13 Ideally, if the biomedical polyelectrolyte coatings are designed with self-healing property, similar to the ubiquitous organism in nature, which can heal injury and recover functionality spontaneously, the biomedical polyelectrolyte coatings can effectively prolong their service life and signicantly improve their reliability. [14][15][16][17] In the past decades, although different styles of self-healing polymeric multilayer coatings have been prepared, [18][19][20] achieving multifunctional biomedical coatings with long service time is also highly desirable for its expansion applications, yet remains an ongoing challenge.…”
Section: Introductionmentioning
confidence: 99%